2020
DOI: 10.1016/j.avsg.2019.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Type 1b Endoleaks After Thoracic Endovascular Aortic Repair are Inadequately Reported: A Systematic Review

Abstract: Background: Complications after thoracic endovascular aortic repair (TEVAR) are common. Even after a successful TEVAR, a late endoleak (>30 days) can occur. The objective of this study is to summarize the current evidence and, if lacking, the need of evidence regarding the incidence and predictive factors for type 1b endoleak in patients with aortic aneurysm treated with TEVAR. Methods: A systematic review of the literature was performed on endoleak type 1b, in patients with aortic aneurysm, after TEVAR. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…It is difficult to compare our series to other endovascular procedures in the thoracic aorta, given that even in TEVAR procedures, the incidence of type 1b endoleak has not been quantified owing to a lack of published data. 13 We have clearly demonstrated that appropriate oversizing and sealing length of the distal stent results in decreased postoperative endoleak and need for reintervention. In some of these cases, preoperative selection of a larger distal stent may have prevented endoleak.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is difficult to compare our series to other endovascular procedures in the thoracic aorta, given that even in TEVAR procedures, the incidence of type 1b endoleak has not been quantified owing to a lack of published data. 13 We have clearly demonstrated that appropriate oversizing and sealing length of the distal stent results in decreased postoperative endoleak and need for reintervention. In some of these cases, preoperative selection of a larger distal stent may have prevented endoleak.…”
Section: Discussionmentioning
confidence: 74%
“…It is difficult to compare our series to other endovascular procedures in the thoracic aorta, given that even in TEVAR procedures, the incidence of type 1b endoleak has not been quantified owing to a lack of published data. 13 …”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis reports the incidence of EL-Ib as up to 8%. 33 Interestingly, none of the evaluated articles reported on the influence of DLZ length. Furthermore, no study mentioned evaluated IFU adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Complications after TEVAR are not rare. The reported incidence of type Ib endoleak 1 year after TEVAR is between 1.0% and 15.0%, with a tortuous aorta being a predictor of endoleak [327] and therefore require surveillance.…”
Section: Post Tevar Follow-upmentioning
confidence: 99%